MHD Mixed Convection Flow of a Micropolar Fluid Past a Wedge Fixed in a Fluctuating Free Stream and Surface Temperature (Dhaka University Journal of Science, 2016)
The flow an  heat transfer on the unstea y laminar mixe  convection boun ary layer in a micropolar flui  past a vertical we ge have been stu ie  taking into account the effect of magnetic fiel . We assume that the free stream velocity an  surface temperature oscillate in magnitu e but not in the  irection of the oncoming flow velocity. The governing equations have been solve  numerically by using the straight forwar  finite  ifference metho . The amplitu es of skin friction an  couple stress are foun  to be significantly  epen ent on the Richar sons number, Ri, the magnetic parameter, M, an  the vortex viscosity parameter, K. We observe that the amplitu es of skin friction an  couple stress increases owing to an increase of the Richar sons number, Ri, while these become lower for the higher value of the magnetic parameter, M, an  the vortex viscosity parameter, K. Also the results  emonstrate that the effects of the parameters on the amplitu es of heat transfer are rather weak. Dhaka Univ. J. Sci. 64(1): 65-70, 2016 (January)